ICS educational module: Pressure flow study in children. Issue 8 (21st June 2018) - Wen, Jian G.; Djurhuus, Jens C.; Rosier, Peter F.W.M.; Bauer, Stuart B.
Abstract : Aims: To introduce the standard procedure and results interpretation of pressure/flow study (PFS) in children. Methods: The literature on PFS in children in PubMed for the last 20 years was reviewed. The updated knowledge on PFS in children in children regarding indication, preparation, technique, and interpretation were summarized. Results: This educational module explains when and how to do a PFS and how to analyze the results. All requirements and instructions for the PFS in children described in this document follow ICS reports on Good Urodynamic Practice and urodynamic equipment performance as well as guidelines from the ICCS. PFS can be obtained subsequent to filling cystometry with no specific additional equipment (apart from a flowmeter) or patient preparation needed. It requires both vesical and intra‐abdominal pressures being recorded. Information from clinical history, physical examination, voiding diaries, and free uroflowmetry with or without perineal patch EMG and pertinent imaging results should be available before undertaking urodynamic testing. Conclusions: Following ICS and ICCS guidelines, PFS is an easy procedure and a useful tool to provide information on voiding function in children.